Inflectional Affixes in William Shakespeare’s Play Romeo and Juliet - Sri Melawati Hutasoit; Esron Ambarita; Vivi Novalia Sitinjak (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This thesis examines inflectional affixes in William Shakespeare’s Play Romeo and Juliet. The objectives of this study are to find out the types of inflectional affixes in William Shakespeare’s Play Romeo and Juliet based on Fromkin, Rodman & Hyams (2011) theory. This study applied descriptive qualitative method. The results of this study are eight types of inflectional affixes namely third-person singular present, past tense, progressive, past participle, plural, possessive, comparative, superlative. The writer found that there are 18 data categorized into third-person singular present, 10 data categorized into past tense, 2 data categorized into progressive, 8 data categorized into past participle, 13 data categorized into plural, 16 data categorized into possessive, 2 data categorized into comparative and 2 data categorized into superlative.